A Novel Approach for Stock Price Prediction (International Journal of Communication Systems and Network Technologies, 2019)
Stock market has always attracted people from all backgrounds. With great returns stock market investment comes with great risks. In this paper, we propose a time-series prediction model using Long Short Term Memory - LSTM to forecast the stock market trend based on the technical analysis using historical data. We also propose the FB PROPHET model which is more robust in time series forecasting. This model automates the process of forecasting stock market trends helping individuals to buy, sell, or hold their stocks. The obtained results showed the time series prediction model has great potential for short-term predictions.
Keywords: Stock Price Prediction; LSTM; FB Prophet; Time Series Data; Python